2022
DOI: 10.1155/2022/2673972
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Tourism Supply Chain Assessment Using Hybrid Decision-Making Methods under Fuzzy Uncertainty

Abstract: In recent years, sustainable environmental issues have attracted attention from all circles due to environmental variation and the depletion of natural resources. Modern thinking about the environment contains the human environment, historical tradition, and social life of the whole ecosystem. In this research, the design, development, and construction of the environmental system are assessed. In this regard, sustainable development, environmental issues, venue administrators and staff, tourists’ education, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Te nature of products in service sectors such as medical tourism makes word of mouth very powerful with indications of its role in diminishing the inherent risk of such transactions. Te limited research on word of mouth and its role in medical tourism established its infuence on end users and their attraction, with no details of the process except the fact that in medical tourism clientele greatly rely on recommendations from friends and family rather than the internet [45]. It is suggested that end users will rely more on word of mouth regarding medical tourism, while online channels will mostly serve functional roles such as factchecking and bookings.…”
Section: Word Of Mouth In Medical Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…Te nature of products in service sectors such as medical tourism makes word of mouth very powerful with indications of its role in diminishing the inherent risk of such transactions. Te limited research on word of mouth and its role in medical tourism established its infuence on end users and their attraction, with no details of the process except the fact that in medical tourism clientele greatly rely on recommendations from friends and family rather than the internet [45]. It is suggested that end users will rely more on word of mouth regarding medical tourism, while online channels will mostly serve functional roles such as factchecking and bookings.…”
Section: Word Of Mouth In Medical Tourismmentioning
confidence: 99%
“…Te purpose of the current study's interview process was to choose any appropriate and suitable subjects [45]. Te interviews were semistructured and were conducted by native speakers of Farsi and English [57].…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…This method was developed by Saati in 1980. It is known as a powerful and flexible technique for solving complex problems [ 28 ]. The AHP method combines objective and subjective evaluations with an integrated structure based on scales of paired comparisons, and it organizes the essential aspects of a problem with a hierarchical format [ 29 ].…”
Section: Introductionmentioning
confidence: 99%